Giant sialoliths of submandibular gland duct: Report of two cases with unusual shape - Anand Gupta; Divey Rattan; Ruchita Gupta (Wolters Kluwer Medknow Publications, 2013)
Giant sialoliths are classified as those exceeding 15 mm in any one dimension. Although, large sialoliths have been described in the body of salivary glands, they are rarely found in the salivary ducts, particularly when the patients have no painful symptoms. Sialolithiasis is one of the most common diseases of the salivary glands in middle-aged patients and approximately 80% of all reported cases of sialoliths occur in the submandibular gland. Here, we report two cases of giant sialolith of submandibular gland duct. Interestingly, sialolith found in one of our cases had an unusual similarity with the canine tooth and mimicking it in both size and shape. In both cases the calculus was removed surgically via intraoral approach. No recurrence was seen in any of the cases on follow-up.